STAT3 regulates cytokine expression in peripheral blood mononuclear cells from asthma patients - Yang, Q.; Xu, W.; Long, Y.; Kuang, J.; Li, J. (Cellular and Molecular Biology, 2017)
Asthma is a common long term inflammatory disease of the airways. This disease affected millions of people worldwide. Recently, it is demonstrated that signal transducer and activator of transcription 3 (STAT3) plays critical role in asthma occurrence. In the current study, we isolated peripheral blood mononuclear cells (PBMCs) from patients with mild and moderate asthma, and then determined the correlation between STAT3 and cytokine expression. We found that the concentration and mRNA level of cytokines was increased in PBMCs from asthma patients. The concentration and mRNA level of cytokines was altered by the regulation of STAT3 expression and the concentration and mRNA expression level of cytokines was positively correlated with STAT3 activation. Furthermore, phosphorylated STAT3 expression in PBMCs from asthma patients was increased compared with the control. Collectively, this study directly proved that STAT3 was correlated with cytokine expression in PBMCs from asthma patients, providing a potential linkage between STAT3 and pathogenesis of asthma.